How Long Do Housing Cycles Last? A Duration Analysis for 19 OECD Countries - Bracke, Philippe (International Monetary Fund, 2011)
This paper analyzes the duration of house price upturns and downturns in the last 40 years for 19 OECD countries. I provide two sets of results, one pertaining to the average length and the other to the length distribution. On average, upturns are longer than downturns, but the difference disappears once the last house price boom is excluded. In terms of length distribution, upturns (but not downturns) are more likely to end as their duration increases. This duration dependence is consistent with a boom-bust view of house price dynamics, where booms represent departures from fundamentals that are increasingly difficult to sustain